Modelling the Diel Vertical Movement of Swordfish (Xiphias gladius Linnaeus, 1758) Based on Temperature and Depth Recorder Data - Bram Setyadji; Hety Hartaty (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2016)
Understanding the vertical distribution of large pelagic fish, swordfish in particular, could improve our knowledge on its fisheries strategy, management and resource conservation. However the methods often require expensive tools and resources, which probably most scientists from the development countries couldn’t afford. Thus developing model on the diel vertical movement behavior of swordfish using number of hook between float (HBF) and complete-set temperature and depth recorder (TDR) data could be an alternative. In general context, capture depth distributions are a good indicator of the natural depth distribution of the fish if the entire depth range of the species is targeted by longline gear. The proposed sinusoidal model suggested that swordfish showed a diel pattern in depth distribution, marked by remained in the surface and mixed layer waters at night and dived into deeper waters during the day. Keywords: swordfish, behavior, HBF, TDR, sinusoidal model